2021
DOI: 10.3389/fcvm.2021.631817
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Infarction: The Protective Role of MiRNAs in Myocardium Pathology

Abstract: Cardiovascular diseases have been regarded as the leading cause of death around the world, with myocardial infarction (MI) being the most severe form. MI leads to myocardial apoptosis, cardiomyocyte fibrosis, and cardiomyocyte hypertrophy, ultimately leading to heart failure, and death. Micro RNAs (miRNAs) participate in the genesis and progression of myocardial pathology after MI by playing an important regulatory role. This review aims to summarize all available knowledge on the role of miRNAs in the myocard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 128 publications
0
17
0
Order By: Relevance
“…Growing evidence has shown that miRNAs are extensively involved in the pathogenic mechanisms that lead to HF in adult patients, such as hypertrophy, apoptosis and fibrosis [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidence has shown that miRNAs are extensively involved in the pathogenic mechanisms that lead to HF in adult patients, such as hypertrophy, apoptosis and fibrosis [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence has shown that miRNAs are related to cardiac function, disease, and cardioprotection (37)(38)(39)(40). Regarding cardioprotection, the expression of several miRNAs, such as miR-1, miR-21, and miRNA-125b, have been identified to be significantly changed due to ischemic pre-or postconditioning (41)(42)(43)(44).…”
Section: Discussionmentioning
confidence: 99%
“… 128 By binding to the 3’ region of targeted mRNA, miRNAs induce the degradation or silence of that and inhibit the expression of targeted genes. 129 In MI, miRNAs play an essential role in anti-apoptosis or regeneration for cardiomyocytes and inhibition of inflammation for immune cells. Despite significant advances in the use of miRNAs for the regulation of disease pathogenesis, several vital challenges remain to be addressed, ranging from ineffective delivery systems to the continuous host immune response or the potential thrombosis 130 caused by the off-target effects.…”
Section: Nanomaterials For Micro-rna and Stem Cell Deliverymentioning
confidence: 99%